Asymmetric Synthesis of US-FDA Approved Drugs over Five Years (2016-2020): A Recapitulation of Chirality - Rekha Tamatam; Dongyun Shin (MDPI AG, 2023)
Chirality is a major theme in the design, discovery, and development of new drugs. Historically, pharmaceuticals have been synthesized as racemic mixtures. However, the enantiomeric forms of drug molecules have distinct biological properties. One enantiomer may be responsible for the desired therapeutic effect (eutomer), whereas the other may be inactive, interfere with the therapeutic form, or exhibit toxicity (distomer). Classical chemical synthesis usually leads to a racemic mixture unless stereospecific synthesis is employed. To meet the requirements of single-enantiomeric drugs, asymmetric synthesis has evolved at the forefront of drug discovery. Asymmetric synthesis involves the conversion of an achiral starting material into a chiral product. This review emphasizes the methods used for synthesizing FDA-approved chiral drugs during 2016-2020, with a special focus on asymmetric synthesis by means of chiral induction, resolution, or chiral pool.